Strategies for Realizing Independent Villages in Wajo Regency: Identification of Supporting and Obstacle Factors through SWOT Approach - P, Resky Amalia; Akib, Haedar; Jabu, Baso (International Journal of Education, Culture, and Society, 2025)
Village development is an important part of Indonesia's national development policy, with the aim of improving community welfare through village empowerment and self-reliance. Wajo Regency, which has abundant natural resource potential but still faces a number of challenges, is the focus of this research. This research aims to identify the factors that support and hinder the implementation of independent village development in Wajo Regency, as well as formulate appropriate strategies to improve village independence. The method used in this research is a descriptive qualitative approach with a case study, where data was collected through in-depth interviews, field observations, and document analysis. Data analysis was conducted using descriptive qualitative techniques and SWOT analysis, which examines the strengths, weaknesses, opportunities, and threats in the implementation of independent village development. The results showed that supporting factors such as natural resource potential, government policy support, and active community participation, while inhibiting factors include the limited quality of human resources, dependence on village funds, and limited infrastructure. Based on these findings, the proposed strategies include strengthening the quality of human resources, diversifying village income sources, and improving infrastructure and technology to support the sustainability of independent village development in Wajo Regency.